New Synonyms and Lectotypification in Begonia section Australes (Begoniaceae) - Tebbitt, Mark C. (Phytotaxa, 2019)
In preparation for a taxonomic account of Begonia section Australes, Begonia crinita and B. rubricaulis var. volcanensis are here newly synonymized with B. micranthera subsp. micranthera, and lectotypes of Begonia crinita and B. pearcei are designated.